A case report of Pseudotumor Cerebri in pregnancy - Navid Kalani; Maryam Jalali Jahromi; Mehdi Sanatkar; Mohammad Sadegh Sanie Jahromi (Mashhad University of Medical Sciences, 2022)
Introduction: Pseudotumor Cerebri (PTC) is a condition characterized by increased intracranial pressure (ICP). It is mainly found in overweight women of childbearing age. In this study, a case of PTC in pregnancy was reported. Case presentation: The patient was a 26-year-old pregnant woman weighing 70 kg in the 19th week of pregnancy with symptoms of diplopia, headache, and transient visual obscuration who referred to the gynecologist. The gynecologist checked the patient for pregnancy poisoning and after tests, it was determined that she did not have pregnancy poisoning. After referring the patient to an ophthalmologist, the patient was diagnosed with PTC. The treatment form the neurologist's view was drug therapy or LP that the gynecologist did not allow to use drug and LP treatment was selected for the patient. During pregnancy, the patient underwent LP for 9 times. During pregnancy, no drug was prescribed for psedotomor cerebri due to obstruction by a gynecologist and the disease was controlled only by LP. The patient underwent cesarean section under spinal anesthesia by diagnosis of a anesthesiologist and the baby weighed 3400 g was born with a first minute Apgar score of 9 and a fifth minute Apgar score of 10. Conclusion: Although the pathology of psedotomor cerebri has not been fully identified yet, but various treatment methods have been mentioned to prevent the progression of this disease. In the present study, the reported patient was controlled with regular follow-ups and performing LPs. The maternal and fetal complications following somatomerber were well controlled.